Occupational outlook handbook: a review of 50 years of change. - Pilot, Michael J. (Monthly Labor Review, 1999)
At first glance, it is difficult to see great differences between the 1949 and 1998 editions of the Occupational Outlook Handbook. Both volumes contain data about the nature of work; employment; training, qualifications, and advancements; the future of various occupations; and wages and working conditions. Both also give information of finding additional data. A detailed study of the coverage and content of various editions over the last half-century shows substantial changes, however. Some of the major improvements and other changes that have occurred are discussed, in the process illustrating the ever-shifting occupational structure and social environment of the last 50 years.